2005
DOI: 10.1007/s10711-005-3691-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional FC Artin Groups are CAT(0)

Abstract: Building upon earlier work of T. Brady, we construct locally CAT(0) classifying spaces for those Artin groups which are three-dimensional and which satisfy the FC (flag complex) condition. The approach is to verify the 'link condition' by applying gluing arguments for CAT(1) spaces and by using the curvature testing techniques of Elder and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…He showed that these complexes carry a piecewise Euclidean metric of non-positive curvature and have as fundamental group the Artin groups under consideration. A generalisation of this was proved by Bell [2].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…He showed that these complexes carry a piecewise Euclidean metric of non-positive curvature and have as fundamental group the Artin groups under consideration. A generalisation of this was proved by Bell [2].…”
Section: Introductionmentioning
confidence: 72%
“…2b) F is the following edge of rank (1, 2) with dominant vertex v as in (2a) (2c) F is the following edge of rank(1,2) with dominant vertex v as in (2a) (3a) F is a single vertex of rank 3, namely either v = {{1, 2, 3, 5}, {4}, {6}} or v = {{1, 2, 4, 5}, {3}, {6}}(3b) F is the following edge of rank (3, 4) with dominant vertex v as in (3a) Proof. Write v 1 , .…”
mentioning
confidence: 99%
“…It is so because 2-dimensional Artin groups are torsion-free by [CD95b], and their cyclic subgroups are undistorted (see Theorem 1.4 below). Prior to our result solvability of the Conjugacy Problem was established only for a few particular subclasses of Artin groups: braid groups [Gar69], finite type Artin groups [BS72, Del72, Cha92, Cha95], large-type Artin groups [App84,AS83], triangle-free Artin groups [Pri86], 3-dimensional Artin groups of type FC [Bel05], certain 2-dimensional Artin groups with 3 generators [BC02], some Artin groups of Euclidean type [CC05,Dig06,Dig12,McC15,MS17], RAAG's [Ser89,Van94,HM95,CGW09]. In particular, the question about solvability of the Conjugacy Problem has been open for the class of 2-dimensional Artin groups.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning CAT(0) spaces, R. Charney asks whether every Artin-Tits group acts properly and cocompactly on a CAT(0) space (see [Cha]). Very few cases are known, essentially right-angled Artin groups (see [CD95]), groups with few generators (see [Bra00], [BM10], [HKS16]) and groups with sufficiently large labels (see [BC02], [BM00], [Bel05], [Hae19]).…”
Section: Introductionmentioning
confidence: 99%